The lower limit of reactivity as a potential individualised cerebral perfusion pressure target in traumatic brain injury: a CENTER-TBI high-resolution sub-study analysis - Beqiri, Erta; Zeiler, Frederick A.; Ercole, Ari; Placek, Michal M.; Tas, Jeanette; Donnelly, Joseph; Aries, Marcel J. H.; Hutchinson, Peter J.; Menon, David; Stocchetti, Nino; Czosnyka, Marek; Smielewski, Peter; et al. (Critical care, 2023)
Background: A previous retrospective single-centre study suggested that the percentage of time spent with cerebral perfusion pressure (CPP) below the individual lower limit of reactivity (LLR) is associated with mortality in traumatic brain injury (TBI) patients. We aim to validate this in a large multicentre cohort. Methods: Recordings from 171 TBI patients from the high-resolution cohort of the CENTER-TBI study were processed with ICM+ software. We derived LLR as a time trend of CPP at a level for which the pressure reactivity index (PRx) indicates impaired cerebrovascular reactivity with low CPP. The relationship with mortality was assessed with Mann-U test (first 7-day period), Kruskal–Wallis (daily analysis for 7 days), univariate and multivariate logistic regression models. AUCs (CI 95%) were calculated and compared using DeLong’s test.Results: Average LLR over the first 7 days was above 60 mmHg in 48% of patients. %time with CPP < LLR could predict mortality (AUC 0.73, p =  < 0.001). This association becomes significant starting from the third day post injury. The relationship was maintained when correcting for IMPACT covariates or for high ICP. Conclusions: Using a multicentre cohort, we confirmed that CPP below LLR was associated with mortality during the first seven days post injury.
Gesehen am 17.07.2023